2015
DOI: 10.1155/2015/721201
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparummsp2Genotypes and Multiplicity of Infections among Children under Five Years with Uncomplicated Malaria in Kibaha, Tanzania

Abstract: Genetic diversity of Plasmodium falciparum may pose challenges in malaria treatment and prevention through chemotherapy and vaccination. We assessed Plasmodium falciparum genetic diversity and multiplicity of infection (MOI) of P. falciparum infections and sort relationship of parasitaemia with P. falciparum msp2 genotypes as well as with the number of infecting clones. The study was carried out in Kibaha, Tanzania. Ninety-nine children under five years with uncomplicated malaria were recruited. Genetic divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 22 publications
4
25
0
Order By: Relevance
“…This would have provided direct evidence of the association between MOI and the quality of antibody responses. This notwithstanding, the emerging pattern of association between MOI, albeit based on mostly MSP2 allele families, and transmission intensity in malaria endemic areas [ 38 40 , 56 58 ] provides the necessary basis for making the inferences drawn in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would have provided direct evidence of the association between MOI and the quality of antibody responses. This notwithstanding, the emerging pattern of association between MOI, albeit based on mostly MSP2 allele families, and transmission intensity in malaria endemic areas [ 38 40 , 56 58 ] provides the necessary basis for making the inferences drawn in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, it can be hypothesized that individuals who experience simultaneous infection with multiple parasite variants will develop a more cross-reactive antibody profile compared to those who mostly experience clonal infections. A number of studies have demonstrated a greater average number of parasite variants per infected person, expressed as the multiplicity of infection (MOI), under high malaria transmission settings compared to corresponding findings in areas of low transmission [ 38 40 ]. The current study therefore assessed the functional quality of antibody responses in symptomatic and asymptomatic children between the ages of one and five years from an area in the Upper-East Region of Ghana with clearly marked seasonal malaria transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D7 allelic types predominated in all the three study groups as compared to the FC27 allelic types, indicating its dominance in this geographical area. A number of studies conducted in Ghana and Tanzania have identified the 3D7 allelic parasite type to be dominant among the parasite populations [ 18 , 40 , 45 , 46 ]. Different P. falciparum parasite variants may influence gametocyte carriage differently, as was observed in this study where individuals carrying both 3D7 and FC27 allelic types of parasite had a higher risk of harbouring gametocytes compared to single 3D7 or FC27 allelic types.…”
Section: Discussionmentioning
confidence: 99%
“…This findings may suggest the possibility of limited immune responses against these parasite variants due to antigen-specific immunosuppression or immune tolerance, hence their ability to persist for longer periods and commit to gametocyte formation [ 47 ]. However, in other studies, the family-specific FC27 allelic type parasites have been shown to be associated with high parasite densities as well as involved in disease severity, suggesting they may be more pathogenic [ 46 , 48 ]. This underscores the need to investigate the potential role other family allelic type of parasites may play in gametocyte carriage in different study populations and transmission areas, since its effect may impact on transmission.…”
Section: Discussionmentioning
confidence: 99%